A method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights
By adding polymer measuring trigly polypropylene powder to the dual polypropylene powder for physical cross -linking, it solves the problem of increasing the difficulty of dissolving the medium solubility and the difficulty of the spinning process of polypropylene pheneine. Preparation of solid content and high -powered performance.
Patent Information
- Application Number
- CN202411553803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, when increasing the molecular weight of the polyacrylonitrile spinning stock solution, there are problems such as difficult dissolution, difficulty in spinning process, and defects in primary fibers.
By adding a small amount of polymer measuring triglyacrylestylin powder to the dual polypropylene powder with relatively low molecular weight, physical cross -linking is performed to form a relatively random three -dimensional network structure to improve the mechanical properties of polymer materials.
A high -solid -solid -solid polypropylene spinning raw solution of polypropylene pheasine is achieved, which improves the mechanical properties and spinning continuity of the spinning raw liquid.
Smart Images

Figure CN119039626B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dry-process high-molecular-weight polyacrylonitrile, and in particular relates to a method for preparing polyacrylonitrile spinning stock solution by physical cross-linking and dissolving different molecular weights. Background Art
[0002] Carbon fiber is an inorganic fiber with a carbon content of more than 95%. It has a series of excellent properties such as high strength, high modulus, high temperature resistance, fatigue resistance, friction resistance, low density, shock absorption, radiation resistance, and low thermal expansion coefficient. Due to its outstanding performance, it is being used as a high-tech material for both military and civilian use, and is widely used in aviation and military fields such as space shuttles, space probes, and artificial satellites, civil industries such as medical equipment, sports and leisure equipment, and general industrial fields such as aircraft industry, automobile industry, wind power generation, cables, infrastructure, and civil construction.
[0003] Polyacrylonitrile-based carbon fiber is the most promising precursor for producing high-performance carbon fiber. Carbon fiber prepared from polyacrylonitrile has excellent properties such as high tensile strength and high tensile modulus. The preparation of high-performance dry carbon fiber is mainly divided into two steps. The first step is the preparation of polyacrylonitrile (PAN) precursor, which needs to go through the polymerization, degassing, stripping, filtering, spinning, washing, drawing, drying and other processes of the spinning solution; the second step is the pre-oxidation and carbonization of the precursor. To produce high-performance PAN precursor, first prepare high-performance precursor. The simplest method is to increase the relative molecular mass of the polymer in the PAN spinning solution.
[0004] The molecular weight of polyacrylonitrile polymer has a huge impact on the mechanical properties of the precursor fiber. It is reported that high-molecular-weight polyacrylonitrile polymer with a high content can significantly improve the strength and modulus of the precursor fiber. This is mainly because the longer the carbon network length, the higher the strength and modulus of the carbon fiber. The strength of the precursor depends on the intermolecular force. The higher the average molecular weight, the longer the carbon network length of the carbon fiber condensed aromatic ring, and the greater the intermolecular force. Therefore, increasing the molecular weight of the copolymer is conducive to improving the strength of the polyacrylonitrile precursor. Secondly, the increase in molecular weight can effectively reduce the number of end groups of the macromolecular chain, thereby improving the regularity of the fiber structure and reducing the formation of defects during pre-oxidation and carbonization, thereby improving the performance of the carbon fiber.
[0005] In the preparation process of high-performance polyacrylonitrile carbon fiber, the homopolymerized polyacrylonitrile-based precursor has a narrow exothermic peak and concentrated exothermic during pre-oxidation, which is prone to broken fibers. Usually, the molecular structure of PAN is adjusted by introducing suitable comonomers such as itaconic acid (IA) and methyl acrylate (MA) into acrylonitrile monomer (AN) and controlling their content. The ester group in methyl ester can reduce the intramolecular and intermolecular interactions and cohesive energy density through volume effect, thereby improving the solubility and spinnability of PAN and improving the quality of PAN precursor; while the carboxyl group in itaconic acid can promote the cyclization of pre-oxidized fibers, reduce the starting temperature of pre-oxidation, and prepare high-performance dry-process carbon fibers.
[0006] At present, some literatures mention that PAN copolymers with a viscosity-average molecular weight of more than 500,000 are obtained by aqueous precipitation polymerization. Although this method increases the hydrophilicity of the polymer, the initiator - ammonium persulfate has great hidden dangers in storage. It explodes when exposed to high heat or impact, and the production process is difficult to control.
[0007] At present, the way to increase the molecular weight of polyacrylonitrile spinning solution is to first use aqueous precipitation or aqueous suspension polymerization to synthesize PAN particles with a viscosity-average molecular weight of about 500,000-1,000,000, and then dissolve them as component A. Use solution polymerization to synthesize a conventional spinning solution as component B, and then mix A and B to increase the molecular weight of the PAN spinning solution. However, this method has a great disadvantage that it is difficult to fully dissolve A during the dissolution process, and there are many gel blocks in the solution, which can easily cause difficulties in the spinning process, and the primary fibers generated by spinning have many defects.
[0008] High-performance dry-process polyacrylonitrile spinning solution has the characteristics of high relative molecular weight and high solid content, which increases the difficulty of dissolution. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing polyacrylonitrile spinning solution by physical cross-linking and dissolving different molecular weights with simple process, easy operation and high solid content.
[0010] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing polyacrylonitrile spinning solution by physical cross-linking dissolution of different molecular weights, characterized in that it comprises the following steps:
[0011] 1) Prepare binary polyacrylonitrile powder and ternary polyacrylonitrile powder in a mass ratio of 85-98:2-15, pour them into dimethylacetamide solvent and stir them evenly to form uniform binary polyacrylonitrile solution and ternary polyacrylonitrile solution; swell the ternary polyacrylonitrile solution at 60°C-80°C for 1h-6h, and evenly mix the binary polyacrylonitrile solution and the swollen ternary polyacrylonitrile solution to form a paste-like uniform polyacrylonitrile solution;
[0012] 2) The polyacrylonitrile solution is heated and swelled at 60°C~80°C for 1h~4h, then heated to 90°C~100°C and swelled in a second stage, and finally dissolved to obtain the polyacrylonitrile stock solution.
[0013] The invention provides a method for preparing polyacrylonitrile spinning solution by physical crosslinking dissolution of different molecular weights. The process is simple and easy to operate. NN dimethylacetamide is used as a solvent. Under the premise of ensuring a high solid content of the polyacrylonitrile spinning solution, a small amount of high molecular weight ternary polyacrylonitrile powder is added to a binary polyacrylonitrile powder with a low molecular weight, and the mixture is dissolved to cause a physical crosslinking reaction. Non-covalent bonds are formed between polymer chains or inside molecules, and a relatively irregular three-dimensional network structure is formed under the action of supramolecular forces such as hydrogen bonds and van der Waals forces and chain entanglement, thereby giving the polymer material stronger mechanical properties.
[0014] Due to the complex molecular shape and aggregate structure, the dissolution process of polymers is difficult and slow, and needs to go through two stages: swelling and dissolution. Swelling is the process in which the polymer macromolecules, under the action of solvents, continuously weaken the interaction between molecules, and the solvent molecules gradually penetrate into the interior of the macromolecules from the outside to the inside, causing the polymer volume to expand. Dissolution is the process in which macromolecules gradually diffuse into the solvent to form a uniform solution. High molecular weight polymers have long molecular chains, good plasticity and high elasticity. The raw solution is spun, drawn, pre-oxidized, and carbonized to produce carbon fibers with relatively high mechanical strength.
[0015] Preferably, before adding the materials, the polyacrylonitrile powder is flash dried to quickly remove moisture, and dried until the moisture content of the powder is less than 0.5%. The powder is crushed and sieved with a pulverizer and then placed in a dryer to cool to room temperature.
[0016] Preferably, in step 1) of the above preparation method, the molar ratio of AN to MA in the binary polyacrylonitrile powder is 94-97:3-6. This binary polyacrylonitrile powder can optimize the solubility of polyacrylonitrile and the viscosity of the spinning solution, thereby improving the performance of the original silk.
[0017] Preferably, in step 1) of the above preparation method, the molar ratio of AN, MA and IA in the ternary polyacrylonitrile powder is 98:0.7~1.3:0.7~1.3. This ternary polyacrylonitrile powder has better solubility in the solvent, thereby increasing the viscosity of the spinning solution, thereby improving the performance of the original silk.
[0018] The corresponding solid content of the stock solution is configured according to the viscosity-average molecular weight of the polyacrylonitrile powder.
[0019] Preferably, in step 1) of the above preparation method, the viscosity average molecular weight of the binary polyacrylonitrile powder is 63,000 to 70,000.
[0020] Preferably, in step 1) of the above preparation method, the viscosity average molecular weight of the ternary polyacrylonitrile powder is 200,000 to 400,000.
[0021] Preferably, the solid content of the polyacrylonitrile stock solution obtained by the above preparation method is 26.0% to 28.0%.
[0022] Preferably, in step 2) of the above preparation method, the swelling time at room temperature is 2h~4h.
[0023] Preferably, in step 2) of the above preparation method, the heating and swelling temperature is 60° C. to 70° C.; and the heating and swelling time is 2 h to 3 h.
[0024] Preferably, in step 2) of the above preparation method, the dissolution temperature is 85°C to 105°C, preferably 90°C to 95°C; the dissolution time is 4h to 8h, preferably 6h to 7h.
[0025] Preferably, in step 2) of the above preparation method, the stirring speed during room temperature swelling is 160 r / min~240 r / min, preferably 180 r / min~220 r / min; the stirring speed during the two-stage heating swelling and dissolution is 120 r / min~200 r / min, preferably 140 r / min~160 r / min, and the stirring time is consistent with the swelling and dissolution time.
[0026] Since the molecular weights of binary polyacrylonitrile powder and ternary polyacrylonitrile powder are quite different, different dissolution rates during simultaneous dissolution will cause uneven stock solution after dissolution. The present invention adopts the principle of "high first and low later" molecular weight to carry out two-step dissolution.
[0027] Compared with the prior art, the method for preparing polyacrylonitrile spinning stock solution by physical crosslinking dissolution of different molecular weights of the present invention has the following beneficial effects: a small amount of high molecular weight ternary polyacrylonitrile powder is added to a relatively low molecular weight binary polyacrylonitrile powder for mixed dissolution, the molecular chains of the polymer are extended by the principle of physical crosslinking, non-covalent bonds are formed between the polymer chains or inside the molecules, and a relatively irregular three-dimensional network structure is formed under the action of supramolecular forces such as hydrogen bonds and van der Waals forces and chain entanglement, thereby giving the polymer material stronger mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a specific process flow chart for dissolving polyacrylonitrile powder.
[0029] Figure 2 This is a microscope observation image (100x) of the original solution of Example 1.
[0030] Figure 3 This is a microscope observation image (100x) of the original solution of Example 2.
[0031] Figure 4 This is a microscope observation image (100x) of the original solution of Example 3.
[0032] Figure 5 This is a microscope observation image (100x) of the original solution of Example 4.
[0033] Figure 6 This is a microscope observation image (400x) of the original solution of Example 5.
[0034] Figure 7 This is a microscope observation image (400x) of the original solution of Example 6.
[0035] Figure 8 This is a microscope observation image (400x) of the original solution of Example 7.
[0036] Fig. 9 This is a microscope observation image (400x) of the original solution of Example 8.
[0037] Fig.10 This is the microscope observation image (100x) of the original solution of comparative example 1.
[0038] Fig.11 This is the microscope observation image (100x) of the original solution of comparative example 2.
[0039] Fig.12 This is the microscope observation image (400x) of the original solution of comparative example 3.
[0040] Fig.13 This is the microscope observation image (400x) of the original solution of comparative example 4.
[0041] Fig.14 This is a microscope observation image (100x) of the original solution of comparative example 5. DETAILED DESCRIPTION
[0042] The specific method for preparing high-performance dry-process polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights of the present invention comprises the following steps:
[0043] (1) Pour the weighed dimethylacetamide solvent into a container, slowly add a small amount of weighed polyacrylonitrile powder into the solvent in batches, and pour while stirring with a glass rod until the powder is evenly dispersed in the solvent.
[0044] (2) Stir and swell the evenly dispersed ternary polyacrylonitrile solution at room temperature.
[0045] (3) After the terpolymer polyacrylonitrile and dimethylacetamide solvent are uniformly mixed to form a paste-like uniform solution, the temperature is raised to 60°C~80°C to heat swell the original solution.
[0046] (4) After the stock solution is completely swollen and evenly transparent, continue to pour the binary polyacrylonitrile powder into the stock solution in batches, stir evenly, and continue to swell at a temperature of 60℃~80℃ until the stock solution becomes uniform and slightly shiny gelatinous.
[0047] (5) After uniform swelling, continue to raise the temperature to 90℃~100℃ to continue swelling, and finally heat to 85℃~105℃ to dissolve.
[0048] (6) During the polymer swelling and dissolution process, a slow heating method is used, and each temperature zone is kept for at least 30 minutes to ensure uniform dissolution of the polymer.
[0049] (7) When the solution is dissolved and becomes transparent, measure its viscosity using the rotational viscosity method at 80°C.
[0050] The present invention will be described in detail below by way of examples.
[0051] Example 1
[0052] Weigh 120g DMAC, add 0.89g of ternary polyacrylonitrile powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 98:2 of diacrylonitrile powder: ternary polyacrylonitrile powder, evenly disperse it in the solvent, fully swell to translucency at 60℃ and 200r / min, and then add 43.49g of diacrylonitrile powder with a molecular weight of 68,000 to the stock solution. Disperse the powder evenly in the solvent to prepare a 27.0% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by rotational viscosity method.
[0053] Example 2
[0054] Weigh 120g DMAC, add 1.73g terpolymer powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 96:4 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 41.54g dipolymer powder with a molecular weight of 68,300 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.5% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0055] Example 3
[0056] Weigh 120g DMAC, add 2.60g ternary polyacrylonitrile powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 94:6 of diacrylonitrile powder: ternary polyacrylonitrile powder, evenly disperse it in the solvent, fully swell to translucency at 60℃ and 200r / min, and then add 40.67g diacrylonitrile powder with a molecular weight of 65,200 to the stock solution. Disperse the powder evenly in the solvent to prepare a 26.5% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min and swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by rotational viscosity method.
[0057] Example 4
[0058] Weigh 120g DMAC, add 3.43g terpolymer powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 92:8 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 39.39g dipolymer powder with a molecular weight of 68,300 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.3% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0059] Example 5
[0060] Weigh 120g DMAC, add 1.73g terpolymer powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 90:10 of dipolymer powder to terpolymer powder, evenly disperse it in the solvent, fully swell to translucency at 60℃ and 200r / min, then add 38.54g dipolymer powder with a molecular weight of 65,200 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.3% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min and swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0061] Example 6
[0062] Weigh 120g DMAC, add 0.89g of terpolymer powder with a viscosity average molecular weight of 400,000 to the solvent according to the ratio of 98:2 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 43.49g of dipolymer powder with a molecular weight of 63,500 to the stock solution. Evenly disperse the powder in the solvent to prepare a 27.0% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0063] Example 7
[0064] Weigh 120g DMAC, add 1.73g terpolymer powder with a viscosity average molecular weight of 400,000 to the solvent according to the ratio of 96:4 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 41.54g dipolymer powder with a molecular weight of 65,200 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.5% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by rotational viscosity method.
[0065] Example 8
[0066] Weigh 120g DMAC, add 2.60g terpolymer powder with a viscosity average molecular weight of 400,000 to the solvent according to the ratio of 94:6 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 40.67g dipolymer powder with a molecular weight of 65,200 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.3% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0067] Comparative Example 1
[0068] Weigh 120g DMAC, add 44.38g of diacrylonitrile powder with a viscosity average molecular weight of 68,300 to the solvent. Disperse the powder evenly in the solvent to prepare a 27.0% uniform stock solution, swell while stirring at 60°C, adjust the speed to 150r / min and swell for 2h, heat to 70°C and stir for 1h, heat to 80°C and continue stirring for 1h, finally dissolve at 90°C for 6h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0069] Comparative Example 2
[0070] Weigh 120g DMAC, add 3.43g terpolymer powder with a viscosity average molecular weight of 400,000 to the solvent according to the ratio of 92:8 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 39.39g dipolymer powder with a molecular weight of 68,300 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.3% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0071] Comparative Example 3
[0072] Weigh 120g DMAC, add 1.73g terpolymer powder with a viscosity average molecular weight of 400,000 to the solvent according to the ratio of 90:10 of dipolymer powder to terpolymer powder, evenly disperse it in the solvent, fully swell to translucency at 60℃ and 200r / min, then add 38.54g dipolymer powder with a molecular weight of 65,200 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.3% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min and swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, finally dissolve at 90℃ for 5h, and measure the viscosity of the polymerization stock solution by rotational viscosity method.
[0073] Comparative Example 4
[0074] Weigh 120g DMAC, add 5.19g terpolymer powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 88:12 of dipolymer powder: terpolymer powder, and evenly disperse it in the solvent. After fully swelling to translucence at 60℃ and 200r / min, add 38.08g dipolymer powder with a molecular weight of 63,500 to the stock solution. Evenly disperse the powder in the solvent to prepare a 26.5% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min, swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, and finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by the rotational viscosity method.
[0075] Comparative Example 5
[0076] Weigh 120g DMAC, add 6.32g of ternary polyacrylonitrile powder with a viscosity average molecular weight of 200,000 to the solvent according to the ratio of 85:15 of diacrylonitrile powder to ternary polyacrylonitrile powder, evenly disperse it in the solvent, fully swell to translucency at 60℃ and 200r / min, and then add 35.84g of diacrylonitrile powder with a molecular weight of 63,500 to the stock solution. Disperse the powder evenly in the solvent to prepare a 26.0% uniform stock solution, swell while stirring at 60℃, adjust the speed to 150r / min and swell for 2h, heat to 70℃ and stir for 1h, heat to 80℃ and continue stirring for 1h, finally dissolve at 90℃ for 6h, and measure the viscosity of the polymerization stock solution by rotational viscosity method.
[0077] Take 1.2-1.5 g of the dissolved original solution and place it on a flat and clean glass slide, press it into a flat thin slice, boil it in boiling water for 15 minutes to remove the solvent, dry it naturally, and observe the dissolved state of the original solution under a microscope.
[0078] Table 1 shows the spinnability and solubility of the spinning solutions prepared in the examples and comparative examples.
[0079]
[0080] From the test results in the above table and the dissolution state of the original hydraulic sheet, it can be seen that:
[0081] In Examples 1-8 of the present invention, a small amount of high molecular weight ternary polyacrylonitrile powder is added to a relatively low molecular weight binary polyacrylonitrile powder to be mixed and dissolved, and a uniform spinning solution with a solid content of 26% to 27% is prepared by adjusting the molecular weight of the polyacrylonitrile powder, the addition ratio and the dissolution process. Figure 2-Figure 9 The polymer is dissolved evenly, most of it has dissolved, and a small part is in a swollen state. The dissolved stock solution is uniform and transparent, has good viscoelasticity, and good spinning continuity.
[0082] In Comparative Example 1, high molecular weight polyacrylonitrile powder was not added. Fig.10 It can be seen that after dissolution, almost all the polymers in the stock solution are dissolved, and the stock solution is uniform and transparent, but the viscoelasticity is low, which is easy to cause leakage or breakage during the spinning process.
[0083] The proportion of high molecular weight polyacrylonitrile powder added in Comparative Examples 2-5 is relatively high. Figure 11-Figure 14 It can be seen that the polymers in the stock solution are dispersed and aggregated, and most of them have not been dissolved. The stock solution has serious climbing during the dissolution process. After dissolution, the stock solution has high viscosity, is not transparent enough, and has many bubbles. Excessive pressure will be caused during the spinning process, resulting in uneven filament bundles and deformation of the spinneret.
[0084] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights, characterized in that: The steps include: 1) Prepare binary polyacrylonitrile powder and ternary polyacrylonitrile powder in a mass ratio of 90-98:2-10, pour them into dimethylacetamide solvent and stir evenly to form uniform binary polyacrylonitrile solution and ternary polyacrylonitrile solution; The ternary polyacrylonitrile solution is swollen at 60°C to 80°C for 1h to 6h, and the binary polyacrylonitrile solution and the swollen ternary polyacrylonitrile solution are uniformly mixed to form a paste-like uniform polyacrylonitrile solution; The molar ratio of AN to MA in the binary polyacrylonitrile powder is 94-97:3-6; the molar ratio of AN, MA and IA in the ternary polyacrylonitrile powder is 98:0.7-1.3:0.7-1.3; the viscosity average molecular weight of the binary polyacrylonitrile powder is 63,000-70,000; the viscosity average molecular weight of the ternary polyacrylonitrile powder is 200,000-400,000; 2) The polyacrylonitrile solution is heated and swelled at 60°C~80°C for 1h~4h, then heated to 90°C~100°C and swelled in a second stage, and finally dissolved to obtain a polyacrylonitrile stock solution; the solid content of the obtained polyacrylonitrile stock solution is 26.0%~28.0%.
2. The method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights according to claim 1, characterized in that: The swelling time described in step 1) is 2h~4h.
3. The method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights according to claim 1, characterized in that: The heating and swelling temperature in step 2) is 60°C to 70°C; the heating and swelling time is 2h to 3h.
4. The method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights according to claim 1, characterized in that: The dissolution temperature in step 2) is 85°C to 105°C; and the dissolution time is 4h to 8h.
5. The method for preparing polyacrylonitrile spinning solution by physical crosslinking and dissolving different molecular weights according to claim 1, characterized in that: The stirring speed during swelling in step 1) is 160 r / min~240 r / min; the stirring speed during the two-stage heating swelling and dissolution in step 2) is 120 r / min~200 r / min, and the stirring time is consistent with the swelling and dissolution time.
Citation Information
Patent Citations
Method for improving dissolving property of high molecular weight polyacrylonitrile produced by dry method
CN114457448A
Method for improving dissolving property of dry-process high molecular weight polyacrylonitrile spinning solution
CN118407142A